Response of gladiolus genotypes to in vivo inoculation of Fusarium oxysporum f. sp. gladioli on growth, flowering and disease incidence - KUMARI, MEENU; SWAROOP, KISHAN; SINGH, SANJAY K; KAMIL, DEEBA; SINGH, BHUPINDER; BHARADWAJ, C (The Indian Journal of Agricultural Sciences, 2019)
In the present study 30 gladiolus genotypes were evaluated for different traits and reaction to two virulent strains of Fusarium, viz. IARI isolate (F. oxysporum f. sp. gladioli â€“ Fog isolate 1) and Pantnagar isolate (F. oxysporum f. sp. gladioli - Fog isolate 2). The two healthy uniform sized corms were planted in individual pots (12â€) filled with potting mixture (soil: FYM: sand; 2:1:1) in five replications. Before planting, the corms were treated with suspension of Fusarium (3 Ã— 106/ml) for 24 hr. Among the genotypes, Dhanwantri (14.59%), Pusa Unnati (14.59%), Swarnima (16.54%), and hybrid Smokey Lady Ã— Oscar (22.92%) were found tolerant to both the Fusarium isolates. The maximum plant height, spike length, rachis length and mean number of florets/spike were noted in Pusa Unnati, but the earliest spike emergence took place in Jyotsana (87.37 days), earliest opening of first floret was noted in Melody (103.79 days). The maximum mean corm weight (87.58 g) was noted in Jyotsana, while maximum diameter was found in Dhanwantri (6.56 cm). Leaves and corms were sampled at 60 days of planting for estimation of different biochemical parameters, viz., total chlorophyll, total phenol, malondialdehyde (MDA) content and H2O2 peroxidation. The tolerant genotypes had higher levels of leaf total chlorophylls and total phenols. The H2O2 evolution and malondialdehyde (MDA) content showed marked increment due to in vivo inoculation of the pathogen. Correlation studies with plant mortality index (PMI) showed a positive correlation for DSI (0.899), while negative correlations were estimated for MDA content (0.879**) followed by H2O2 formation (0.862**), total phenol (r = 0.810**) and total chlorophyll (r = -0.754**). Results showed that genotypes, namely, Dhanwantri, Pusa Unnati, Swarnima, and hybrid Smokey Lady Ã— Oscar were Fusarium wilt tolerant along with desirable agronomic traits, thus can be recommended for commercial cultivation.